SAT0474 Very low disease activity and impact of disease in a spanish population with psoriatic arthritis. (15th June 2017) - Queiro, R; Cañete, JD; Montilla, C; Abad, MA; Gόmez, S; Cábez, A
Abstract : Background: The target of treatment in psoriatic arthritis (PsA) should be remission or inactive disease. A potential definition that would fit with the Treat-to-Target Recommendations would be MDA meeting all 7 criteria 1, proposed as a definition of very low disease activity (VLDA) in PsA. Patient reported outcomes (PROs), such as those provided by the novel PsAID questionnaire 2, are also important to evaluate healthcare interventions and to reflect the impact of PsA on patients' lives. Objectives: The aims of the present study were to evaluate the prevalence of VLDA in patients with PsA and how much residual active disease is still present, so as to determine whether PsAID could be an additional useful tool to assess PsA interventions in clinical practice. Methods: This was a post-hoc analysis of data from a cross-sectional observational and multicenter study (MAAPS), aimed at evaluating the prevalence of MDA in a Spanish population with PsA, to describe their characteristics and to evaluate the association between MDA and the impact of the disease as assessed by the PsAID questionnaire in routine clinical practice The original study included adult patients of both genders diagnosed with PsA according to CASPAR criteria with at least one year of evolution time of disease and on treatment with biological and/or conventional synthetic disease modifying anti-rheumatic drugs (cDMARD). Patients were considered in VLDA when they met all the MDA criteria 1 : tender joint count ≤1, swollen joint count ≤1, Psoriasis Area Severity index (PASI) score ≤1 or body surface area ≤3%, patient pain visual analog scale (VAS) score ≤15, patient global disease activity VAS score ≤20, Health Assessment Questionnaire (HAQ) score ≤0.5, and tender entheseal points ≤1. Patient acceptable symptoms state (PASS) has been defined as a PsAID value <4. Results: 227 patients were included, 133 (58.6%) in MDA state and 58 (25.6%) in VLDA state. VLDA patients suffered from a mild impact of the disease according to PsAID: the majority (82.5%) had a PsAID score <4 and a mean total score (SD) of 2.1 (2.6) IC95% [1.55–2.64], while, 66.7% of MDA patients had a PsAID score <4 and a mean total score (SD) of 3.3 (3.1) IC95% [2.82–3.87]. Disability, as measured by HAQ was greater in MDA patients (mean (SD) 0.3 (0.5) IC95% [0.21–0.43]) than in those who reached VLDA state (mean (SD) 0.2 (0.3) IC95% [0.11–0.25]. Conclusions: 26% of Spanish PsA patients achieve VLDA state in routine clinical practice. PsA patients who reached this state also had a very low impact of disease according to PsAID. VLDA state could represent a situation of clinical remission in PsA. References: Coates LC, Fransen J, Helliwell PS. Ann Rheum Dis 2010;69(1):48–53. Gossec L, de WM, Kiltz U, Braun J, Kalyoncu U, Scrivo R et al. Ann Rheum Dis 2014;73(6):1012–1019. Acknowledgements: MAAPS (Minimal Activity in Psoriatic Arthritis) study group:. J.C. Torre Alonso; J.A Román Ivorra; J. Sanz; J. Salvatierra; J. Calvo Alén; A. Sellas; F.J. Rodriguez; A. Bermúdez; M.Romero; M. Riesco; J.C Cobeta; F.Medina; A. Aragόn; ML. García; A. Urruticoechea; CM. González; E. Judez; B. González; P. Fernández; L. Pantoja; R. Morlá. This study was funded by Pfizer. Disclosure of Interest: None declared